Mental Health and Psychotropic Stigma Among Student Pharmacists - Brandy Davis; Cassidi C. McDaniel; Chih-hsuan Wang; Kimberly B. Garza (Frontiers Media S.A., 2022)
ObjectiveTo gain a better understanding of student pharmacists' stigma toward mental health and psychotropic medications.MethodsA cross-sectional study was conducted via paper and online surveys amongst all student pharmacists enrolled in a Doctor of Pharmacy program in the Southeastern United States (n = 501). The Perceived Devaluation and Discrimination (PDD) Scale was used to measure mental health stigma. The Beliefs about Medicines Questionnaire (BMQ) was modified to measure psychotropic stigma. MANOVAs were conducted to investigate relationships between student pharmacists' characteristics with mental health and psychotropic stigma. A paired t-test was used to determine if there was a difference between degree of mental health stigma and psychotropic stigma.ResultsA total of 390 participants completed the survey (65%). The sample was mostly female (67%), white (79%), and non-Hispanic (96%). Ages were predominantly within the 19-24-year range (80%), and the majority of respondents reported previous interactions with patients who have mental health conditions (55%) or patients on psychotropic medications (65%). Student personal preferences for mental health treatment were primarily psychologic (42%) or both psychologic and psychotropic (40%). Degree of psychotropic stigma was significantly greater than that of mental health stigma. A statistically significant association was found between student personal preference for treatment and the psychotropic stigma. No difference was found in degree of either type of stigma across cohorts.ConclusionsStudent pharmacists demonstrated both mental health and psychotropic stigmas. Future research should be performed to determine what effects these stigmas have on care of patients with mental health conditions.